Geofence untuk Deteksi Virtual Perimeter pada Aset Daerah Irigasi - Rachmat Wahid Saleh Insani (Universitas PGRI Kanjuruhan Malang, 2020)
Irrigation Area is a region consisting of an irrigation network aimed to improve agricultural products' effectivity and efficiency. In every development and refinement phases of the irrigation network, monitoring and preservation proceeds for every irrigation asset is a must. Floodgates, natural rivers, primary canals, secondary canals, tertiary canals, and collector canals are the irrigation assets. One of the essential data for the asset irrigation surveyors while conducting assets monitor and maintain is the geolocation data. For each irrigation areas and their assets are in multiple areas with difficult to accessed and observed. Hence, the geolocation data for every irrigation area's border and the asset's location point obtained while neglecting accurate. Therefore, monitoring and maintaining asset also obstructed as inaccurate geolocation data. Geofence is a virtual perimeter technology constitute geolocation data point with radius in a circle on the digital map. This research proposed a virtual perimeter detection system for irrigation asset locations with geofence technology. The irrigation asset data we used are from Kubu Raya Regency, West Borneo Province. The system runs in the Android operating system as the surveyor could use the geolocation data directly on the field.